Repression in the Existential Lives of Dostoevsky’s Poor People - Ramirez, Jesús (Labyrinth, 2021)
This paper explores Sigmund Freud's concept of repression in the existential strife exhibited by two main characters, Makar Alexyevitch and Varvara Alexyevna, in Fyodor Dostoevsky's Poor People. To demonstrate this, I psychoanalyze of how they handle their repressed desires, emphasizing the necessity of Freud's main rule for this method: Openness. Dostoevsky's Poor People presents an existential crisis handled through openness and mishandled when an individual represses one's desires. In delving into Dostoevsky's first novel, I demonstrate a link between the existential and psychological, wherein individuals strive to overcome themselves. Surprisingly, this link has a come a common influence between Dostoevsky and Freud: Immanuel Kant. I briefly discuss this shared similarity to show the basic idea of an "existential middle" derived from a Freudian psychoanalysis of Dostoevsky's Poor People.